Investigation of Factors Affecting Discharge Capacity of Prefabricated Vertical Drains - Sengul, Tayfun; Edil, Tuncer; Ozaydin, Kutay (TURKISH CHAMBER CIVIL ENGINEERS, 2013)
An important factor affecting the performance of PVDs is their discharge capacity. The effect of factors such as, the hydraulic gradient, lateral stresses on a PVD, the type of soil in which PVDs are placed, the structure of PVDs and their flexural stiffness were investigated. Four different types of PVDs were used to investigate the effects of PVD deformation during the consolidation of soil and clogging of the core area on the discharge capacity of PVDs. The discharge capacity of PVDs, which is large at low deformations, decreases significantly (up to 57%) within the range of hydraulic gradients applied in this study (0.10 to 1.00). At large deformations, PVDs have a lower discharge capacity although the change in hydraulic gradient has a negligible effect on them. On the other hand, experimental observations have shown that the deformations occurring during consolidation of soils have an important effect on the discharge capacity of PVDs. For the type of PVDs used, the discharge capacity decreases by 68% to 100% when PVDs deform by 41.5%. Furthermore, a 40% decrease in discharge capacity is observed when lateral stress is increased from 25 kPa to 200 kPa. Clogging of the core zone, shapes of deformation, structure of PVD, and resistance against buckling have varying effects on the discharge capacity of PVDs depending on the soil type.
Keywords: Prefabricated vertical drain; model testing system for discharge capacity; discharge capacity of prefabricated vertical drains; IMPROVEMENT; Engineering